Evaluasi Program Pembelajaran Ilmu Pengetahuan Sosial (IPS) Intensive Science Class (ISC) MAN Darussalam Ciamis Jawa Barat - Majidah, Rima (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2020)
This research was motivated by the establishment of the Intensive Science Class (ISC) Social Science (IPS) learning program which is a relatively new learning program in MAN Darussalam Ciamis, West Java. This study aims to describe how the process, supporting and inhibiting factors and also the results of the evaluation of the Social Sciences (IPS) Intensive Science Class (ISC) learning program through the Stake countenance evaluation model. This research is an evaluative qualitative research. The results of this study indicate that: (1) Implementation of evaluation of learning programs has been motivated by a fairly clear introduction (antecedent), because there are considerations on vision, mission, and goals, processes (transactions) that have been good and results (outcomes) are quite good, because there are considerations on student achievement results. (2) The inhibiting and supporting factors of the learning program that consists of 5 (five) supporting factors and 2 (two) inhibiting factors. (3) The results of the evaluation of the learning program have the result of consideration that is still carried out with improvements.